IMPLEMENTASI FASILITAS BELAJAR ERGONOMIS DI TAMAN KANAK-KANAK - Luciana Triani Dewi; Chandra Dewi K; I Wayan Gede Digda Sukmawan; Mario Dwi Kurnianto (Universitas Sanata Dharma, 2019)
The partner of this program is a kindergarten in Sleman District, DIY whose condition is still limited. Teaching and learning facilities were limited and some of them in unfit conditions. Based on the observation, two problems were encountered related to the availability of learning facilities. The first problem was the unavailability of facilities for students’ bags and stuff temporary placed during the lesson running. Students put bags and stuff on a rack of potluck or scattered in the classroom hall. The second problem was the unavailability of a cabinet to display student work and as a place to store educational toys. The shelf used did not satisfy the user and was unable to display the student work and store the toy properly. The solution provided was the implementation of ergonomic lockers and also display and store cabinet. Stages of the program covered design, manufacture, implementation, mentoring and evaluation. The implementation of new facilities leads to positive benefits for teachers and students. The facilities support a better process of teaching and learning. Teacher and students can interact with the implemented facilities safely, healthily, comfort, effectively and efficiently.